42.03=9g+3.96

Simple and best practice solution for 42.03=9g+3.96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42.03=9g+3.96 equation:



42.03=9g+3.96
We move all terms to the left:
42.03-(9g+3.96)=0
We get rid of parentheses
-9g-3.96+42.03=0
We add all the numbers together, and all the variables
-9g+38.07=0
We move all terms containing g to the left, all other terms to the right
-9g=-38.07
g=-38.07/-9
g=4+2.07/9

See similar equations:

| M^2-4m+140=180 | | 0=X^3-4x^2-5x+20 | | 255w=2000-w/0.2 | | 255w=2000(-w/0.2) | | 50=10+5x^2 | | 120÷6=n | | (2x-5)/4=(x+5)/5 | | -21+11r=-11(-r+3) | | 24-2x)³=0 | | −19+3x+12−x=11 | | 10^3y/10^7=10^11 | | x+7.5*2=15 | | 0=7x4-10x2+10 | | .5n+34=-2(1–7n) | | -10a^2+4a+1=0 | | 10(x–1)=2(2x–5) | | 0.69x+25=1.19x | | F(n)=1 | | 0.69x+25=1.19 | | -62.5=-12w-w/2 | | X×2x=2700 | | x+8=7x+13 | | 35+100+0.45x=100+0.55x | | 6(3x+9)+3=12x+3 | | -8+i/6=2 | | 35+15+100x=40+100x | | 2x+3x-5)+(4x+2)=65 | | 100+15+0.45x=100+0.55x | | -7x+2(x+6)=-33 | | -5a+6(2a+7)=12 | | (17x+8)(10x+57)=180 | | 6-(n+3)=3n+5-22 |

Equations solver categories